Effect of maternal body mass index on pregnancy outcome: a retrospective observational study at a secondary level care hospital in India - Ghosal, Adrija; Rashmi,; Akhtar, Selim; Das, Bibekananda; Bhattacharya, Tushar Kanti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Maternal BMI outside the range of 18.5 to 24.9 is associated with adverse maternal and/or foetal outcome. In India, due to extreme socioeconomic distribution, double burden of malnourishment & obesity is being observed, though it varies from state to state. Many studies are conducted showing association of obesity with pregnancy outcome, while importance of underweight is not studied frequently in our geographical area, hence this study was planned to be conducted. Methods: Our aim was to evaluate the maternal and perinatal outcomes in patients belonging to different BMI categories. We performed retrospective observational study at department of obstetrics and gynaecology, Suri Sadar Hospital, a secondary level care hospital at Birbhum, West Bengal, India between July 2021 to May 2022. Sample size taken was 170. Detailed data were collected from the MCP card (maternal child protection card) of the mothers, antenatal follow up sheets of these women and hospital medical records. The study participants were then divided into 5 groups according to their first trimester BMIs. Statistical analysis was carried out with the help of Micro soft Excel and Epiinfo 7.1 software, p<0.05 were considered significant. Results: Average mean weight gain in our study was 9.1118 kg and we found significant association between weight gain during pregnancy & BMI status (p<0.001). We also observed significant association of gestational diabetes mellitus, preeclampsia, caesarean section, pre-term labour, post-partum haemorrhage, post-partum wound infection with obese & overweight mother. FGR and MAS were also found to be significantly associated with maternal BMI. Complex maternal metabolic environment on developing foetus in obese mother alone or complicated by PIH or GDM may be the cause. In underweight mother, malnutrition and micronutrient deficiency may lead to development of FGR. Conclusions: Pre conceptional normal BMI is essential for every woman willing to conceive. Nutrition-sensitive programs like food security, poverty alleviation, women education, women empowerment, dietary consultation for all newly married couples is required for developing countries to prevent altered pre pregnancy BMI.